Specific IgE and IgG4 Profiles of House Dust Mite Components in Allergen-Specific Immunotherapy - Yang, Lin; Yang, Yaqi; Xu, Qingxiu; Zhang, Wei; Jiang, Qing; Li, Wenjing; Wang, Yin; Ma, Dongxia; Lin, Xiaomin; Sun, Baoqing; Zhu, Rongfei (Frontiers in Immunology, 2022)
Background: Allergen immunotherapy (AIT) can induce immune tolerance to allergens by activating multiple mechanisms, including introduction of regulatory T and B cells, promotion of IgG4-associated blocking antibodies synthesis, and blunting IgE production. The development of component-resolved diagnosis (CRD) in allergology allow us to analyze IgE and IgG4 antibodies at molecular level. However, the longitudinal data of sIgE and sIgG4 to allergen components during AIT are limited. Objective: We sought to investigate the persistence and evolution of sIgE and sIgG4 against house dust mite (HDM) components during AIT and explore their correlation with clinical responses. Methods: Sixty allergic rhinitis (AR) with/without asthma patients receiving AIT for HDM were enrolled in AIT group. Thirty AR patients without receiving AIT were served as control group. Blood samples were collected for sIgE, sIgG4 to HDM components (Der p 1, Der f 1, Der p 2, Der f 2, Der p 7, Der p 10, Der p 21 and Der p 23) assay at baseline, 6-month and 18-month of AIT. Combined symptom and medication scores (CSMS) were obtained accordingly. Results: In the AIT group, sIgG4 to the HDM components of Der p 1, Der f 1, Der p 2 and Der f 2, Der p 21 significantly increased at 18-month compared to the baseline (36.2 U/mL vs 158.8 U/mL, 46.4 U/mL vs 94.6 U/mL, 80.5 U/mL vs 152.3 U/mL, 78.3 U/mL vs 205.1 U/mL, 42.3 U/mL vs 59.3 U/mL, all P<0.05), sIgE to HDM components didn’t see differences at baseline and 18-month (all P>0.05). The numbers of positive HDM component sIgE and sIgG4 increased from 4.5 to 5 and 0 to 1.5 respectively (both P<0.05). However, the changes of sIgE, sIgG4, sIgE/sIgG4 ratio and the numbers of positive HDM components had no correlations with the improvement of CSMS after AIT (all ρ<0.3). Conclusion: AIT can induce the production of sIgG4 to HDM components. However, the increased sIgG4 levels of HDM component do not correlate with the corresponding sIgE levels at baseline and AIT response. sIgG4 to HDM components are not qualified as a biomarker to evaluate the efficacy of AIT.